2004
DOI: 10.1186/1472-6955-3-2
|View full text |Cite
|
Sign up to set email alerts
|

The factors facilitating and inhibiting effective clinical decision-making in nursing: a qualitative study

Abstract: BackgroundNurses' practice takes place in a context of ongoing advances in research and technology. The dynamic and uncertain nature of health care environment requires nurses to be competent decision-makers in order to respond to clients' needs. Recently, the public and the government have criticized Iranian nurses because of poor quality of patient care. However nurses' views and experiences on factors that affect their clinical function and clinical decision-making have rarely been studied.MethodsGrounded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 19 publications
1
107
0
4
Order By: Relevance
“…The results of these qualitative studies indicate that clinical experience was one of the most critical influences on the overall decision-making process (Bakalis, 2006;Traynor, Boland, & Buus, 2010). Researchers from the United Kingdom, United States, and Iran found that education had a positive effect on nurses' CDM (Hagbaghery, Salsali, & Ahmadi, 2004;Prescott, Dennis, & Jacox, 1987;Rhodes, 1985). Bucknall (2003) concluded that three important environmental influences on nurses' real decisions in the critical care setting in Australia were patient situation, physical and personnel resource, and interpersonal relationships.…”
Section: Factors Influencing Nurses' Cdm Skillsmentioning
confidence: 94%
“…The results of these qualitative studies indicate that clinical experience was one of the most critical influences on the overall decision-making process (Bakalis, 2006;Traynor, Boland, & Buus, 2010). Researchers from the United Kingdom, United States, and Iran found that education had a positive effect on nurses' CDM (Hagbaghery, Salsali, & Ahmadi, 2004;Prescott, Dennis, & Jacox, 1987;Rhodes, 1985). Bucknall (2003) concluded that three important environmental influences on nurses' real decisions in the critical care setting in Australia were patient situation, physical and personnel resource, and interpersonal relationships.…”
Section: Factors Influencing Nurses' Cdm Skillsmentioning
confidence: 94%
“…A health care provider possessing high confidence levels in the areas of communication and clinical (physical) skills is of paramount importance because of greater patient outcome expectancies seen by those who are assessed and treated by providers who possess higher levels of confidence. 27,28 Being confident is one of the most important personal factors influencing clinical decision making, 29 because if a clinician believes that he or she has the skills to assess a patient's concerns and that the outcome of this assessment will lead to an improved quality for the patient, it is more likely that the clinician will engage in a successful assessment. 30 This applies across all health care professions including chiropractic practice.…”
Section: Professional Confidence In Health Care Researchmentioning
confidence: 99%
“…It is the real environment in which students find the opportunity to test their knowledge and skills [24]. The fact that the students use their knowledge about the SH/RH topics integrated into the curriculum in the clinical environment (Table 1; item 8) is evidence that knowledge has been translated into behavior [25] and that the project has proved successful. It might also be said that the successful results were attained because a new skills laboratory was set up and the support shown the project made it possible to use the school's own resources to complete the installation of tools and equipment.…”
Section: Discussionmentioning
confidence: 98%